Estimation of Multipath Propagation Delays and Interaural Time Differences from 3-D Head Scans - Gamper, Hannes; Thomas, Mark; Tashev, Ivan (IEEE Intl. Conf. on Acoustics, Speech and Signal Processing (ICASSP), 2015)
The estimation of acoustic propagation delays from a sound source to a listener’s ear entrances is useful for understanding and visualising the wave propagation along the surface of the head, and necessary for individualised spatial sound rendering. The interaural time difference (ITD) is of particular research interest, as it constitutes one of the main localisation cues exploited by the human auditory system. Here, an approach is proposed that employs ray tracing on a 3-D head scan to estimate and visualise the propagation delays and ITDs from a sound source to a subject’s ear entrances. Experimental results indicate that the proposed approach is computationally efficient, and performs equally well or better than optimally tuned parametric ITD models, with a mean absolute ITD estimation error of about 14us.